A REPORT ON THE OCCURRENCE OF SOME ENDOPARASITIC HELMINTHS IN SELECTED FISH SPECIES OF TENALI, GUNTUR DISTRICT, ANDHRA PRADESH, INDIA - M. ARUNA,; ANU PRASANNA VANKARA,; MANI GUDIVADA, (The Bioscan, 2011)
The study was conducted to investigate the occurrence of parasites in selected fish species of Tenali region, Guntur District, Andhra Pradesh. A total of 174 fish specimens including Anabas oligolepis Bleeker, Catla catla Hamilton, Channa punctatus Bloch, Cirrhinus mrigala Linnaeus, Labeo rohita Hamilton and Mastacembelus armatus Lacepede were examined for the parasites from 2009-2010. Only three species, Genarchopsis goppo Ozaki, 1925; Camallanus sp. from Channa punctatus and a metacercaria of Clinostomum gideoni Bhalerao, 1942 from Anabas oligolepis were obtained. The other four fish species showed no infection with the helminths. The present study reveals that parasite diversity of freshwater fishes in this area is very poor and might be due to the nutritive habitat and healthy nature.